Pengembangan Media Pembelajaran Articulate Storyline Berbasis PBL Pada Materi Sistem Pencernaan Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Nasution, Aziz Husein; Adlini, Miza Nina (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop Articulate Storyline learning media based on Problem Based Learning (PBL) on the digestive system material to improve students' creative thinking skills. The study used the Research and Development (R&D) method with the 4D model (Define, Design, Develop, and Disseminate). The subjects were 32 grade XI students of SMAN 2 Plus Panyabungan in the even semester of the 2024/2025 Academic Year. The research instruments included expert validation sheets, teacher and student response questionnaires, and creative thinking essay tests based on indicators of fluency, flexibility, originality, and elaboration. Data were analyzed through validity, practicality, and effectiveness tests using the N-Gain calculation. The results of the study indicate that the PBL-based Articulate Storyline media developed is in the very valid category based on the assessment of material experts and media experts, very practical according to teacher and student responses, and effective in improving creative thinking skills with an N-Gain value of 0.71 (effective). This media is considered easy to operate, interesting, interactive, and able to motivate students to be active in learning. Thus, the PBL-based Articulate Storyline media on the digestive system material is proven to be valid, practical, and effective in supporting students' creative thinking skills, and can be an innovative alternative in improving the quality of biology learning according to the demands of the 21st century.